2021
DOI: 10.5811/westjem.2021.3.50266
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Landmark-guided Glenohumeral Joint Injections as Assessed by Ultrasound in Anterior Shoulder Dislocations

Abstract: Introduction: To determine the accuracy of landmark-guided shoulder joint injections (LGI) with point-of-care ultrasound for patients with anterior shoulder dislocations. Methods: Patients with anterior shoulder dislocations who underwent LGI were enrolled at our tertiary-care and trauma center. LGI attempts were recorded by an ultrasound fellowship-trained ED physician who determined if they were placed successfully. Pain and satisfaction scores were recorded. Results: A total of 34 patients with anterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…We also found no differences in complications between the techniques. Our results were consistent with previous research indicating that an intra-articular lidocaine injection is safe with a low risk of neurovascular injury [12,18]. However, although previous articles support the idea that the risks of infection and chondrolysis are low [5,6,8,14], we cannot definitively state this because both complications typically occur after an extended amount of time, and our study only had a 2-week follow-up period.…”
Section: Length Of Stay In the Emergency Department And Complicationssupporting
confidence: 91%
“…We also found no differences in complications between the techniques. Our results were consistent with previous research indicating that an intra-articular lidocaine injection is safe with a low risk of neurovascular injury [12,18]. However, although previous articles support the idea that the risks of infection and chondrolysis are low [5,6,8,14], we cannot definitively state this because both complications typically occur after an extended amount of time, and our study only had a 2-week follow-up period.…”
Section: Length Of Stay In the Emergency Department And Complicationssupporting
confidence: 91%
“…This might be because IAA may not have been administered appropriately. A previous study reported that landmark‐guided IAA administered local anesthetics to inappropriate points in 41.1% of cases, as assessed using ultrasound 31 . Moreover, ultrasound‐guided IAA can be used to administer local anesthetics to the appropriate point 31 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that landmark‐guided IAA administered local anesthetics to inappropriate points in 41.1% of cases, as assessed using ultrasound 31 . Moreover, ultrasound‐guided IAA can be used to administer local anesthetics to the appropriate point 31 . Therefore, under conditions of adequate pain relief, the IAA method has the potential to achieve a lower pain score than that of the IVS method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was not reported if this was because they were old and at high risk for drugs use or because of ED overcrowding. A previous study showed that landmark‐guided shoulder joint injections were misplaced in 41.1% of cases by EPs [ 18 ]; the success rate of the interscalene brachial plexus nerve block by EPs was 71% [ 19 ]; shoulder dislocation reduction required a moderate depth of sedation [ 20 ]. Our study did not record pain score and sedation depth, although the 15 patients who used sedatives or analgesics may have had inadequate pain relief or sedation.…”
Section: Discussionmentioning
confidence: 99%